A review on fuel economy standard for motor vehicles with the implementation possibilities in Malaysia - Mahlia, Teuku Meurah Indra; Saidur, Rahman; Memon, Liaquat Ali; Zulkifli, N.W.M.; Masjuki, Haji Hassan (Elsevier, 2010)
This paper focused on a review of international experiences on fuel economy standard based on technologies available. It also attempts to identify savings possibilities and greenhouse gas (GHG) emissions reductions. It is known that road transport, particularly private cars are responsible for large, and increasing share of transport fuel use and emissions. With the implementation of fuel economy standard and label for motor vehicles, it will reduce the risks of increasing dependency on petroleum-based fuel and will increase the profit to consumers. The GHG emissions, which causing global warming, air pollution, diseases, etc. can be reduced as well. In this regard, advanced technologies such as, engine, transmission, and vehicle technologies may brought significant consumers and social benefits. Studies in developed countries have shown that fuel economy standard is beneficial for the society, government as well as the environment.